Hepatoprotective effect of Pterocarpus marsupium against carbon tetrachloride induced damage in albino rats - Devipriya, D. (Medknow Publications & Media Pvt Ltd, 2007)
Medicinal plants play a key role in human health care. Pterocarpus marsupium is one of the plants used in treatment of diabetes mellitus and the present study was aimed to assess hepatoprotective effect of the plant against CCl(4) induced hepatotoxicity. Wistar albino rats were divided into four groups. Group I was normal control group; Group II, the hepatotoxic group was given CCl(4) (2ml/kg body weight intraperitoneally); Groups III received CC1(4) + Plant extract (100 mg/kg b.w orally); Group IV received only the plant extract. Liver markers were assayed in serum and liver tissue. Levels of marker enzymes such as alanine transminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), and lactate dehydrogenase (LDH) and bilirubin were increased significantly in Group II. These enzymes were significantly decreased in Group III treated with plant extracts. The present investigation suggest that the plant had a good protective effect on CCl(4) induced hepatic injury.